2022
DOI: 10.3390/vaccines10081224
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Survey on BNT162b2 mRNA COVID-19 Vaccine Serious Adverse Events in Children 5 to 11 Years of Age: A Monocentric Experience

Abstract: Objective: Our aim was to evaluate the safety of COVID-19 vaccine in children resident in the Latina Local Health Authority. Methods: We conducted a telephone survey among children aged 5–11 years receiving BNT162b2 mRNA COVID-19 vaccine between December 15 and 21. The main outcomes included the presence of allergic reactions or anaphylaxis, adverse events after 24–48 h, 7 and 20 days of taking the first and second doses of medications, and documented SARS-CoV-2 infection after vaccination. The information obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…Finally, we included 2 RCTs and 15 observational studies, including 12 cohort studies and 3 case-control studies (Figure 1). [12][13][14][15]19,20,[31][32][33][34][35][36][37][38][39][40][41][42] Baseline characteristics are summarized in Table 1 and eTable 1 in Supplement 1. There were 10 935 541 vaccinated children (mean or median age range, 8.0-9.5 years; 46.0%-55.9% female individuals) and 2 635 251 unvaccinated children (mean or median age range, 7.0-9.5 years; 44.3%-51.7% female individuals).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, we included 2 RCTs and 15 observational studies, including 12 cohort studies and 3 case-control studies (Figure 1). [12][13][14][15]19,20,[31][32][33][34][35][36][37][38][39][40][41][42] Baseline characteristics are summarized in Table 1 and eTable 1 in Supplement 1. There were 10 935 541 vaccinated children (mean or median age range, 8.0-9.5 years; 46.0%-55.9% female individuals) and 2 635 251 unvaccinated children (mean or median age range, 7.0-9.5 years; 44.3%-51.7% female individuals).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the duration of AEs, the RCTs showed that the median duration of each symptom ranged from 1 to 2 days, except for local pain and redness, which lasted for 3 days or more . Another prospective cohort study showed that 4 of 449 children (0.8%) had symptoms 7 days after the second injection, including headache and lymphadenopathy …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in a real-world setting, Bloise et al recently evaluated the safety of the mRNA COVID-19 vaccines through a prospective, cross-sectional study. Specifically, the authors reported that the systemic adverse effects reported 24–48 h after the first dose were headache (8.1%) and fever (2.9%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%